Musik Diaspora dalam Perayaan Thaipusam Sebagai Ekspresi Budaya Komunitas India Tamil di Kota Medan - Reihan Nabilah Fashah; Eli Irawati; Haryanto (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
Diaspora is the phenomenon of the dispersion of members of an ethnic group, nation, or religious community who migrate and settle in various parts of the world outside their homeland. Although far from their country of origin, they continue to maintain their identity and emotional ties with their ancestral land. Medan, as one of the major cities in Indonesia, is home to diverse ethnic groups, including the Tamil Community originating from Tamil Nadu, South India. The Tamil community has contributed to the development of plantations and cultural life in Medan. Initially, they came as laborers, but now they have become part of the local society while still preserving their traditions, including the celebration of Thaipusam. During the Thaipusam celebration in Medan, there is distinctive Tamil music brought from Malaysia to accompany the ceremony. Musical instruments such as the nadaswaram and thavil serve as a link between the Tamil community and their ancestral culture. This music also introduces the richness of Tamil culture to the Indonesian people. The research uses a qualitative approach from an ethnomusicological perspective. The results show that diaspora music not only functions as part of the ritual but also helps introduce Tamil culture to the broader Indonesian society.